EXCLUSIVE BREASTFEEDING IN PREVENTING STUNTING BASED ON MAKASSAR CITY REGIONAL REGULATION NUMBER 3 OF 2016 ON MAQĀṢID AL-SYARĪ’AH PERSPECTIVE (CASE STUDY OF MAKASSAR HAJI HOSPITAL AND PUBLIC HEALTH CENTER OF TAMALATE) - Muttazimah,; Abdul Halim Talli,; Muhamamad Suhufi, (International Journal of Islamic Studies, 2022)
This study deals with Maqashid Syariah examining Makassar City Regional Regulation No. 3 of 2016 concerning providing Exclusive Breastfeeding to prevent stunting. This study used field research with descriptive research and qualitative research methods. The source of data in this study was field data in the form of interviews with the Head of the public health center or hospital, midwives, breastfeeding counselors, and mothers who have babies. Furthermore, the data collection methods used observation, interviews, and documentation. Then, techniques processing and data analysis were carried out through three stages: data reduction, data presentation, and conclusion. The results showed that the method of exclusive breastfeeding in preventing stunting started with the mother consuming healthy food before and during pregnancy. The implementation of the Makassar City Regional Regulation Number 3 of 2016 concerning exclusive breastfeeding in preventing stunting at the Tamalate Health Center has been carried out well. Exclusive breastfeeding contains maqāṣid arūriyyah; it refers to maintaining religion (al-dīn), soul (al-nafs), mind (al-’aql), descendant (al-nasab), and property (al-māl). Based on the contents of the Makassar City Regional Regulation No. 3 of 2016, the researchers found the existence of maqāṣid arūriyyah, especially arūriyatul khoms.